Trade relations between India and China: A case study of growing economic interdependence between the two biggest markets. - Gouri Gopal Amle. (2008)
India and China, the two biggest markets in the world, have been the focus of my study in this thesis. My paper comprises of four sections. My first section discusses the concept of economic interdependence and globalization, which go hand in hand. Both these concepts are two sides of the same coin. The theory of Economic interdependence given by the liberals and the realist thinkers has been discussed here. According to liberals, “economic interdependence lowers the likelihood of war by increasing the value of trading over the alternative of aggression: interdependent states would rather trade than invade”1, whereas realism argues that “high economic interdependence increases rather than decrease the probability of war”2. The process of globalization gives rise to the economic interdependence. Liberalization is necessary to enhance economic interdependence among nations.